Differential functional role of alpha-4-beta-2 and alpha-7 nicotinic receptors on human natural killer cells - Zanetti, Samanta Romina (2017)
Nicotinic acetylcholine receptors (nAChRs) are pentameric ligand-gated ion channels of the Cys-loop receptor family that serve as targets for acetylcholine and nicotine. nAChRs can be homomeric, which are assembled from five identical subunits, such as α7, or heteromeric, which are assembled from different subunits, such as α4β2. Although nAChRs have been studied mainly at the neuromuscular junction and in neurons, immune cells express several nAChR subunits but the functional relevance of the extra-neuronal cholinergic system remains still undefined.